Pieniądz lokalny - Reichel, Janusz (Local Money, 2007)
The starting point of the paper is the crucial role of the efficient economy for the local development. The author presents examples of using local money for improving the efficiency of transaction system in local community. Certain kinds of such local money systems are based on virtual money. The paper presents advantages from implementing such systems.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 520-530